Does long term low impact stress cause population extinction?. (January 2017) - Amorim, M.J.B.; Pereira, C.; Soares, A.M.V.M.; Scott-Fordsmand, J.J.
Abstract: This study assessed and monitored 40 consecutive reproduction tests - multigenerational (MG) - of continuous exposure to Cd (at 2 reproduction Effect Concentrations (EC): EC10 and EC50) using the standard soil invertebrate Folsomia candida, in total 3.5 years of data were collected. Endpoints included survival, reproduction, size and metallothionein (MTc) gene expression. Further, to investigate adaptation to the toxicant, additional standard toxicity experiments were performed with the MG organisms of F6, F10, F26, F34 and F40 generations of exposure. Exposure to Cd EC10 caused population extinction after one year, whereas populations survived exposure to Cd EC50. Cd induced the up-regulation of the MTc gene, this being higher for the higher Cd concentration, which may have promoted the increased tolerance at the EC50. Moreover, EC10 induced a shift towards organisms of smaller size (positive skew), whereas EC50 induced a shift towards larger size (negative skew). Size distribution shifts could be an effect predictor. Sensitivity increased up to F10, but this was reverted to values similar to F0 in the next generations. The maximum Cd tolerance limits of F. candida increased for Cd EC50 MG. The consequences for risk assessment are discussed. Graphical abstract: Highlights: F. candida was exposed to Cd in 40 consecutive reproduction tests (3.5 years multigenerational-MG). EC10 (32 mg Cd/kg) caused population extinction after one year, while EC50 (60 mg Cd/kg) survived. Size distribution shifts could explain extinction (EC10: positive skew, EC50: negative skew). Higher metallothionein levels for EC50 exposed could be a survival strategy. Maximum Cd tolerance limits of F. candida increased for Cd EC50 MG. Abstract : Low impact stress can cause population extinction.